Digital neutron/gamma discrimination with an organic scintillator - Berikov, D.B.; Ahmadov, G.S.; Kopatch, Yu.N.; Zhumadilov, K.Sh.; Kuznetsov, V.L. (Recent Contributions to Physics, 2019)
The paper presents the results of neutron-gamma discrimination using organic stilbene scintillator. Stilbene scintillations are characterized by a fast rise time (~1 ns), and their decline is characterized by the existence of a fast (for compton electrons from gamma-quanta) and a slow (for recoil protons from fast neutrons) component. A well-known PSD (pulse shape discrimination) method of simultaneous measurement of the total charge and the part of this charge in the tail of the pulse, is proposed for identifying particles. An analog-to-digital converter of the TsRS-32 type was used to convert neutron and gamma-ray pulses and to store them in a digital format. An algorithm has been developed in the C ++ and ROOT programming languages for digital data processing. Stilbene-based detectors are planned to be used in an experiment to study T-odd effects for given particles in the fission of heavy nuclei induced by polarized neutrons. Experimental work was carried out in the I.M. Frank Laboratory of Neutron Physics Joint Institute for Nuclear Research.
Keywords: Neutron-gamma pulse shape discrimination; T-odd effects in the fission of heavy nuclei